Public Services in Banyuwangi Regency, East Java, Indonesia in a Just and Civilized Humanity Perspective - Hary Priyanto; Bambang Soepeno; Edy Wahyudi; Abubakar Eby Hara (Budapest International Research and Critics University, 2021)
The implementation of public services must be ideal and uphold the dignity of the target community. Dissatisfaction due to the phenomenon of convoluted and slow service, reprisals by bureaucrats, siding with the interests of the applicant is known, and